Genetic diversity and population structure of terapon jarbua (ForskÃ¥l, 1775) (teleostei, terapontidae) in malaysian waters - Shyama Sundari Devi Chanthran; Phaik-Eem Lim; Yuan Li; Te-Yu Liao; Sze-Wan Poong; Jianguo Du; Muhammad Ali Syed Hussein; Ahemad Sade; Richard Rumpet; Kar-Hoe Loh (Pensoft Publishers, 2020)
A background study is important for the conservation and stock management of a species. Terapon jarbua is a coastal Indo-Pacific species, sourced for human consumption. This study examined 134 samples from the central west and east coasts of Peninsular (West) Malaysia and East Malaysia. A 1446-bp concatenated dataset of mtDNA COI and Cyt b sequences was used in this study and 83 haplotypes were identified, of which 79 are unique haplotypes and four are shared haplotypes. Populations of T. jarbua in Malaysia are genetically heterogenous as shown by the high level of haplotype diversity ranging from 0.9167–0.9952, low nucleotide diversity ranging from 0.0288–0.3434, and high FST values (within population genetic variation). Population genetic structuring is not distinct as shown by the shared haplotypes between geographic populations and mixtures of haplotypes from different populations within the same genetic cluster. The gene flow patterns and population structuring observed among these regions are likely attributed to geographical distance, past historical events, allopatric speciation, dispersal ability and water currents. For instance, the mixture of haplotypes revealed an extraordinary migration ability of T. jarbua (>1200 km) via ancient river connectivity. The negative overall value of the neutrality test and a non-significant mismatch distribution are consistent with demographic expansion(s) in the past. The median-joining network concurred with the maximum likelihood haplotype tree with three major clades resolved. The scarcity of information on this species is an obstacle for future management and conservation purposes. Hence, this study aims to contribute information on the population structure, genetic diversity, and historical demography of T. jarbua in Malaysia.